Time to Surgery and Its Impact on Outcome in Hip Fracture Patients - Muhammad Zahid Iqbal, Waseem Ahmad, Shoaib Ahmad (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Hip fractures are a common injury among the elderly, associated with significant morbidity, mortality, and healthcare burden. Early surgical intervention has been proposed to improve clinical and functional outcomes, but delays are common in resource-constrained settings. Objective: To determine the effect of time to surgery on clinical and functional outcomes in patients presenting with hip fractures. Methods: This observational study was conducted Department of Orthopaedic Surgery, BBSTH/ DHQ Hospital Abbottabad during from October 2022 to September 2023. A total of 80 patients aged ≥18 years with intertrochanteric or femoral neck fractures were enrolled using consecutive sampling. Patients were categorized into early surgery (≤48 hours from admission) and delayed surgery (>48 hours) groups. Preoperative assessment included demographic data, comorbidities, and baseline functional status. Standard surgical fixation (dynamic hip screw or hemiarthroplasty) was performed, followed by early mobilization and routine postoperative care. Primary outcomes included postoperative complications, length of hospital stay, and in-hospital mortality. Secondary outcomes were time to mobilization and functional status at follow-up. Data were analyzed using t-tests and chi-square tests with significance set at p < 0.05. Results: Early surgery was associated with significantly shorter time to mobilization (3.2 ± 1.1 vs. 5.6 ± 1.8 days, p < 0.001) and reduced hospital stay (7.8 ± 2.4 vs. 11.5 ± 3.1 days, p < 0.001). Functional outcomes were better in the early surgery group, with higher rates of excellent recovery (47.6% vs. 21.1%, p = 0.009). Postoperative complications were lower in the early group, though mortality differences were not statistically significant. Conclusion: Early surgical intervention within 48 hours of admission improves functional outcomes, reduces complications, and shortens hospital stay in hip fracture patients. Prioritizing timely surgery is crucial, particularly in resource-limited settings. Keywords: Hip fracture, Time to surgery, Functional outcome, Postoperative complications